Bovine Milk Allergens: A Comprehensive Review. Issue 1 (13th November 2017) - Villa, Caterina; Costa, Joana; Oliveira, Maria Beatriz P.P.; Mafra, Isabel
Abstract: Cow milk allergy is one of the most common food allergies in early childhood and often persists through adult life, forcing an individual to a complete elimination diet. Milk proteins are present in uncounted food products, such as cheese, yogurt, or bakery item, exposing allergic persons to a constant threat. Many efforts have been made to overcome this global problem and to improve the life quality of allergic individuals. First, proper and reliable food labeling is fundamental for consumers, but the verification of its compliance is also needed, which should rely on accurate and sensitive analytical methods to detect milk allergens in processed foods. At the same time, strategies to reduce milk allergenicity, such as immunotherapy or the use of food processing techniques to modify allergen structure, have to be extensively studied. Recent research findings on the applicability of food processing, such as heat treatment, fermentation, or high pressure, have revealed great potential in reducing milk allergenicity. In this review, significant research advances on cow milk allergy are explored, focusing on prevalence, diagnosis, and therapy. Molecular characterization of cow milk allergens and cross‐reactivity with other nonbovine milk species are described, as well as the effects of processing, food matrix, and digestibility on milk allergenicity. Additionally, analytical methods for the detection of milk allergens in food are described, from immunoassays and mass spectrometry methods for protein analysis to real‐time polymerase chain reaction for DNA analysis.